AL-MU'TAQADÂT NAHW TA'ALLUM AL-LUGHAH AL-‘ARABIYYAH BI WASHFIHÂ LUGHAH AJNABIYYAH 'INDA AL-MUTA'ALLIMÎN 'ABR IKHTILÂF AL-KHALFIYYAH AL-TSAQÂFIYYAH - Nurul Wahdah; Moh. Ainin; M. Abdul Hamid (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2017)
This study aimed at investigating students’ beliefs about Arabic language learning across cultural background differences. The study used a questionnaire of Horwitz’s Beliefs about Language Learning (BALLI). The data were analysed by frequency, arithmetic means and independent sample test. The results indicated that the dimensions of Dayakese students’ beliefs including aptitude, difficulty, and nature of language learning, learning strategies were at a medium level, the dimension of motivation was high, while the dimension of Banjarese including difficulty, nature of language learning, learning strategies and motivation were medium, aptitude was high. Overall, beliefs about Arabic language learning of Dayakese and Banjarese students were medium.  From independent sample test, it was known that the p-value =0.174. This means that there was not a significant difference between Dayakese and Banjarese students. This indicated that the differences among people whose cultures are closed to each other demographically in their beliefs about Arabic language learning were not found.